(untitled) (MAUSAM, 1951)
Convergence in northwest motion without north-suth gradient of velocity or due to variation of coriolis parameter in geostrophic equation is termed as latitudinal convergence. In this paper the orders of vertical velocity and rainfall arising from such convergence are computed and it is known that they are small in tropics.